1993
DOI: 10.1126/science.8446902
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional View of Precursor Messenger RNA Metabolism Within the Mammalian Nucleus

Abstract: A quantitative three-dimensional analysis of nuclear components involved in precursor messenger RNA metabolism was performed with a combination of fluorescence hybridization, immunofluorescence, and digital imaging microscopy. Polyadenylate [poly(A)] RNA-rich transcript domains were discrete, internal nuclear regions that formed a ventrally positioned horizontal array in monolayer cells. A dimmer, sometimes strand-like, poly(A) RNA signal was dispersed throughout the nucleoplasm. Spliceosome assembly factor SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
219
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(235 citation statements)
references
References 38 publications
14
219
2
Order By: Relevance
“…Newly synthesized heteronuclear RNA and small nuclear RNA are enriched on the nuclear matrix [Huang and Spector, 19911. The nuclear matrix has also been shown to be the site of attachment for products from RNA cleavage and for RNA processing intermediates [Carter et al, 1993;Xing et al, 19931. Spliceosome complexes involved in the regulation of RNA splicing have been localized to the nuclear matrix.…”
Section: N a Organization A N D The Nuclear Matrixmentioning
confidence: 99%
“…Newly synthesized heteronuclear RNA and small nuclear RNA are enriched on the nuclear matrix [Huang and Spector, 19911. The nuclear matrix has also been shown to be the site of attachment for products from RNA cleavage and for RNA processing intermediates [Carter et al, 1993;Xing et al, 19931. Spliceosome complexes involved in the regulation of RNA splicing have been localized to the nuclear matrix.…”
Section: N a Organization A N D The Nuclear Matrixmentioning
confidence: 99%
“…It was the observation that the nuclear matrix is composed of a broad spectrum of cell-type and tissue-specific proteins, as well as hnRNAs [Fey and Penman, 1988;Nickerson et al, 1990;Getzenberg and Coffey, 1990a;Fey et al, 1984a;Nickerson and Penman, 1992;Berezney, 1991;Berezney and Coffey, 1975;Fey et al, 1984b;Feyet al, 1988;Penman, 1991;Getzenberg et al, 1991a,b;Wan et al, 19941, which provided compelling evidence for nuclear matrix participation in the regulation of gene expression. Further indications for contributions of the nuclear matrix to regulation of gene expression includes sites for DNA replication Berezney, 1991;Berezney and Coffey, 1975;Hozak et al, 1993;Pienta et al, 19911, preferential association with actively transcribed genes [Nelkin et al, 1980;Robinson et al, 1982;Schaack et al, 1990;Stief et al, 1989;Zenk et al, 1990;Cockerill and Garrard, 1986;Dworetzky et al, 1992;Gasser and Laemmli, 1986;Ward and Coffey, 19901, RNA synthesis at fixed transcriptional complexes and pre-mRNA splicing Lawrence et al, 1989;Zeitlin et al, 1987;Carter et al, 1993;Xing and Lawrence, 1991;Spector et al, 1991;Spector, 1990;Xing et al, 1993;Fey et al, 1986;Penman, 19911, as well as specific association of some but not all steroid hormone receptors [Barrack and Coffey, 1983;…”
Section: Introductionmentioning
confidence: 99%
“…This probe also labeled the same late phase clusters that contain snRNP (compare g and h). Oligo dT probes have been previously shown to label the splicing factor rich interchromatin granule network in uninfected cells (Carter et al, 1991(Carter et al, , 1993Visa et al, 1993, see also Fig. 4 h).…”
Section: Spliced Viral Rnas and Polyadenylated Rnas Are Present In Lamentioning
confidence: 99%
“…Perichromatin fibrils are thought to be the in situ forms of newly synthesized hnRNA. Interchromatin granules are not strongly labeled by a pulse of [3H]uridine and are therefore not likely to be locations of transcription, but several studies have shown that polyadenylated RNA is present in these structures (Carter et al, 1991(Carter et al, , 1993Visa et al, 1993). SnRNP and several nonsnRNP splicing factors accumulate at both perichromatin fibrils and interchromatin granules, raising the possibility that splicing of precursor RNA may occur at these locations.…”
mentioning
confidence: 99%